ZHAKHANSHA DOSMUKHAMEDOV WAS THE FOUNDER OF CIVIL LAW IN THE KAZAKH REGION (Journal of actual problems of jurisprudence, 2020)
The emergence and development of civil law as an independent branch of law was associatedwith the development of commodity-money relations and first developed in ancient Rome. Romanlaw was formed on the basis of customary law as well as the judicial practice of masters who resolvedproperty disputes. Therefore, it was in Roman law that the main provisions of modern civil law werefirst formed. A powerful impetus to the development of civilistic thought was the rapid development ofcommodity-money relations in the Russian Empire. The high level of development of civil law science inpre-revolutionary Russia influenced the formation of civil law in the Kazakh region. A prominent socialand political figure, professional lawyer, one of the leaders of «Alash», the head of the Western branch of«Alash-Orda», Zhakhansha Dosmukhamedov was at the forefront of the development of civil law thoughtin the territory of modern Kazakhstan. His political and legal views were formed under the influence ofprogressive ideas of representatives of the Kazakh intelligentsia, Russian socio-political thought of the19th – early 20th centuries, Western thinkers and lawyers. In this article, the author first examined therole of Zhakhanshi Dosmukhamedov as a civilist in the formation and development of civil law in theKazakh region. Also the autorth identified main stages of him political and legal views.Key words: state, legislation, civil law, civil law relations, contract law, politics, law, autonomy,republic, rule of law.